Custom baked murder - Mugavero, Liz (Mugavero, Liz. Pawsitively organic mystery., 2017)
"Summer is winding down in Frog Ledge, Connecticut, but Stan's love life and career are both heating up nicely. In between planning her new pet patisserie and café, Stan is settling into living-in-bliss with sexy pub owner Jake McGee. Love's on the menu for Stan's mom, Patricia, too, who's engaged to Frog Ledge's mayor, Tony Falco. Mayor Falco's dogged ambition isn't popular among locals, but it's his executive coach, Eleanor Chang, who's inspired a dangerous grudge. When Eleanor is found dead, there's a whole pack of suspects to choose from. Stan has first-hand experience of Eleanor's unsavory business tactics. But finding out who forced her to take a fatal plunge off the corporate ladder means unearthing some shady secrets and a killer who's too close for comfort." --Publisher's description.